Plagued by confusion. (December 2021) - Galloway, Ian; Allen, John; Read, Frank
Abstract : A response to Nick England's letter "Going in circles" and Alan Calverd's and Tim Watson's letters "Weighty issue" concerning the common misunderstandings about circular motion and weight.